Clear-water scour at pile groups - Lança, Rui (2013)
Groups of piles are frequently used as bridge foundations. Different group configurations, characterized by different pile spacing, skew-angle, number, and arrangement of pile group columns interact differently with the flow field and lead to different scour patterns and equilibrium scour depth. There have been a number of past studies on the characterization of scouring at pile groups, but most of them report short duration scour experiments. A priori, such short durations may be postulated to inherently carry important uncertainties into existing scour predictors. In this study, 75 long-duration laboratory tests were run under steady, clear-water flow close to the threshold for initiation of sediment motion, to address the effect of time, pile spacing, skew-angle and number of pile group columns on the equilibrium scour depth. Pile groups consisted of matrical arrangements of one, two, or three columns of four rows, with spacings of 1, 2, 3, 4.5, and 6 pile diameters; the tested skew-angles were 0, 15, 30, 45, and 90°. Important contributions were achieved on (1) the impact of the duration of tests on the shape of the scour hole as well as on the precision of coefficients involved in current predictors, (2) the most unfavorable skew angle, (3) the behavior of collapsed pile groups, (4) the maximum scour depth at pile groups composed of a single alignment, and (5) the performance of two current predictors of scour depth at pile groups. Two formulations of a predictor for the calculation of an aggregated pile group factor are suggested.